Evaluation of Root Canal Morphology of Permanent Maxillary Canine Using CBCT – A Cross-sectional Study - Nor Masitah Mohamed Shukri1, Mahesh Ramakrishnan2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background : A clear understanding and thorough knowledge of anatomy of human teeth is the utmost of importance to all dental procedures especially in endodontic and orthodontics treatment. This includes the study of root canal anatomy and its variations according to the race and gender.Aim : The scope of the research was to determine the root and canal morphology of the maxillary canine in Indian population by analyzing cone-beam computed tomography (CBCT) images.Material and Method : Forty-six CBCT images consisting of 20 males and 26 females were examined in this study and a total of 88 maxillary canines were analyzed. The root anatomy of each tooth was evaluated for the following parameters: the root canal patterns, the shape of the access cavity, the mesiodistal width of the crown and the distance from occlusal pit to the pulp chamber. The data was analyzed and compared and p-value of the data was considered 0.05 statistically.Result : It can be concluded that a higher prevalence of maxillary canines have Type I root canal pattern in both gender. The most common shape of access cavity in male subjects was oval. Round access cavity was the most frequently observed in female subjects. Maxillary canine in male population also had greater mesiodistal crown diameter than female population.Conclusion : The present study reported the normal anatomy and variations of maxillary canines in Indian population. The incidence of root canal morphology differed with gender.